2003
DOI: 10.1300/j029v12n03_03
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences and Psychosocial Factors Associated with Alcohol Involvement and Dysphoria in Adolescence

Abstract: Correlations between Alcohol Involvement, Dysphoria, and their combined effects, with Social Conformity, Perceived Opportunity, Relationship Satisfaction, parental divorce, and Family Support/Bonding were examined with Structural Equation Modeling in a community sample of late adolescents (males = 290, females = 606). Results revealed gender differences between Alcohol Involvement and Dysphoria. Girls had an affectively-involved style of alcohol use that was reflected in a second-order construct, while Alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Similarly, the National Comorbidity Survey reported that the comorbidity rate between alcohol use and affective disorders was higher for women than men (Kessler et al, 1997). Being consistent with this finding, heavy drinking was found to be a risk factor for later depressive symptoms among adolescent girls but not among adolescent boys (Locke & Newcomb, 2003;Poulin, Hand, Boudreau, & Santor, 2005). Perhaps this was partly because female teenagers were more likely to be socially stigmatized for underage use of alcohol than their male counterparts as heavy drinking would not have been considered to be within normal female gender roles (Way et al, 1994).…”
Section: Gender and Deviant Coping Efficacysupporting
confidence: 55%
“…Similarly, the National Comorbidity Survey reported that the comorbidity rate between alcohol use and affective disorders was higher for women than men (Kessler et al, 1997). Being consistent with this finding, heavy drinking was found to be a risk factor for later depressive symptoms among adolescent girls but not among adolescent boys (Locke & Newcomb, 2003;Poulin, Hand, Boudreau, & Santor, 2005). Perhaps this was partly because female teenagers were more likely to be socially stigmatized for underage use of alcohol than their male counterparts as heavy drinking would not have been considered to be within normal female gender roles (Way et al, 1994).…”
Section: Gender and Deviant Coping Efficacysupporting
confidence: 55%
“…Martin, Lynch, Pollack, and Clark (2000) found gender differences in levels of negative emotionality but gender similarities in the degree of association between negative emotionality and alcohol problems. Using cross-sectional data, we (Locke & Newcomb, 2000) found that negative affect (dysphoria) and alcohol use were related for adolescent females but not for males. Negative affect has also been studied as a mediator between stressful life events and alcohol consumption (Hussong & Chassin, 1993).…”
Section: Negative Affect and Alcohol Usementioning
confidence: 99%
“…A negative relationship between family attachment and problem behaviors has been demonstrated (Galaif et al, 2007). For late adolescent males more than late adolescent females, less family support was related to alcohol involvement (Locke & Newcomb, 2003). Low levels of shyness have been associated with substance use (Santesso, Schmidt & Fox, 2004) and tobacco smoking leading to cannabis use (Creemer et al, 2009); whereas, Kellam, Ensminger, and Simon (1980) indicated that moderate to severe shyness was associated with lower cannabis use.…”
Section: Introductionmentioning
confidence: 99%
“…Department of Health & Human Services [USDHHS] 2009). Cigarette use by youth began to decline in the late 1990s, with the rate of decline slowing between 2003(CDC, 2010d, but continues to be unacceptably high (Park et al, 2008). Male adolescents, more than female adolescents, smoke before the age of 13 and smoke more often (Centers for Disease Control & Prevention (CDC), 2009a).…”
mentioning
confidence: 99%